Extensive Presentation of Central Ossifying Fibroma Treated with Conservative Surgical Excision - Matheus Henrique Lopes Dominguete; Alexandre Augusto Sarto Dominguette; Bruno Henrique Matos; Paulo Roberto Dominguete; Jorge Esquiche León; Lucinei Roberto Oliveira (Case Reports in Dentistry)
Central ossifying fibroma is a benign slow-growing tumor of mesenchymal origin and it tends to occur in the second and third decades of life, with predilection for women and for the mandibular premolar and molar areas. Clinically, it is a large asymptomatic tumor of aggressive appearance, with possible tooth displacement. Occasionally treated by curettage enucleation, this conservative surgical excision is showing a recurrence rate extremely low. The objective of this study was to report a case of a 44-year-old woman, presenting a very large ossifying fibroma in the mandible, which was successfully treated with curettage, and to conduct a brief literature review of this lesion, focusing on the histology, clinical behavior, and management of these uncommon lesions.